Alchemy of secrets : a novel - Garber, Stephanie (Flatiron Books, 2025)
"The HOTLY ANTICIPATED adult debut novel by the beloved, #1 NEW YORK TIMES BESTSELLING author of the Caraval and Once Upon a Broken Heart series It starts with a class in an old movie theater. Folklore 517: Local Legends and Urban Myths, taught by a woman called the Professor. Most students believe the Professor's stories are just fiction, but Holland St. James has always been convinced that magic is real. When she tracks down a local legend named the Watch Man, who can supposedly tell you when you'll die, the world finally makes sense. Except that the Watch Man tells her she will die at midnight tomorrow unless she finds an ancient object called the Alchemical Heart. With the clock ticking, Holland is pulled deeper into this magical world in the heart of Los Angeles-and into the path of a magnetic stranger. Everything about him feels like a bad idea, but he promises Holland that her sister sent him to protect her. As they chase clues and stories that take them closer to the Alchemical Heart, Holland realizes everyone in this intoxicating new world is lying to her, even this stranger. And if she can't figure out whom to trust, not even the Alchemical Heart will save her"-- Provided by publisher.